Desarrollo de los criterios de reparabilidad de marcas premium en función al sustrato (2017)
The development of the project it began with the summary of information relating to the materials and present processes in the vehicles of premium brands, suppliers specialized in own equipments of this segment of vehicles and own information of the investigated brands. An analysis of information was realized, there were established the pieces that need specialized procedures, these procedures were established, to proceed to identify the equipments and tools necessary for the correct substitution or repair according to the substratum. During the whole process of the project there was born in mind the average environmental impact, especially in the processes needed in the repair or substitution of pieces of these cars.